Božo Milošević’s sociological themes in Sociološki pregled/ Sociological review - Milošević Šošo, Biljana č; Vukajlović, Mile M (Sociološki pregled, 2018)
The authors point to the contribution of Božo Milošević’s to Serbian sociological thought, through his scientifc papers published in the journal Sociološki pregled/ Sociological Review, since the end of the 1980s until today. His contribution is mostly reﬂected in the advancement of the theoretical foundations of the Sociology of Work, without neglecting any other sociological topics necessary for essential understanding of contemporary social processes and relations.
Keywords: Božo Milošević; Sociološki pregled/ Sociological Review; sociology of work; professionalization